2019
DOI: 10.1042/bst20190081
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory role of the extracellular matrix protein tenascin-C in neuroinflammation

Abstract: The extracellular matrix (ECM) consists of a dynamic network of various macromolecules that are synthesized and released by surrounding cells into the intercellular space. Glycoproteins, proteoglycans and fibrillar proteins are main components of the ECM. In addition to general functions such as structure and stability, the ECM controls several cellular signaling pathways. In this context, ECM molecules have a profound influence on intracellular signaling as receptor-, adhesion- and adaptor-proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 101 publications
2
32
0
Order By: Relevance
“…Our investigations of immunized WT and Tnc deficient mice lead to the assumption that Tnc promotes immunomodulatory processes of the neurotoxic M1-subtype in turns of higher activity. This is in line with previous reports that Tnc supports the activity of M1-microglia ( 36 , 111 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our investigations of immunized WT and Tnc deficient mice lead to the assumption that Tnc promotes immunomodulatory processes of the neurotoxic M1-subtype in turns of higher activity. This is in line with previous reports that Tnc supports the activity of M1-microglia ( 36 , 111 ).…”
Section: Discussionsupporting
confidence: 93%
“…In regard to the temporal induction, Tnc expression levels were enhanced 3 days post injury and returned to normal levels 7 and 14 days after the induction of brain laser lesion ( 73 ). In the CNS, Tnc is re-expressed under pathological conditions and represents an important component of the glial scar ( 11 , 25 , 36 , 74 76 ). In Alzheimer's disease, Tnc immunoreactivity is highly associated with amyloid-β plaques ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, progress has been seen in studies on glioma, among which TNC has shown promise and may play a critical role in glioma pathology. TNC has been revealed to be associated with various aspects of neuron biology, such as the promotion and repression of synapses, neuroinflammation, and neural stem cell and glial progenitor cell proliferation and differentiation (Gottschling et al 2019;Wiemann et al 2019;Faissner et al 2017). In particular, a few findings indicate that TNC might be involved in glioma pathogenesis; however, these findings are far from conclusive.…”
Section: Discussionmentioning
confidence: 99%